Caracterização genotípica do vírus da hepatite B no estado de Roraima - Barros, Jacqueline de Aguiar (2014)
The infection by hepatitis B virus (HBV) is a public health problem in Brazil and worldwide. Subpopulations of 10 genotypes of HBV (defined from A to J) circulate worldwide, showing a heterogeneous distribution. Growing evidences relate HBV’s genotypes to the clinical differences presented by infected individuals, such as the disease pathogenesis, viremia, mutant’s appearance, response and resistance to antiviral treatment. Roraima integrates western Amazon, considered of high prevalence to hepatitis B. However, there are not studies that characterize the infection and the circulating genotypes in this population. The objective of this study was describing the epidemiological and genotype profile of chronic infection by hepatitis B virus (HBV) in Roraima State. For this, we obtained information to the disease’s epidemiological profile description through the application of a specific survey, through the clinical records and information provided by institutions and information’s systems that compose Viral Hepatitis Network Services in Roraima state. The genotypes were determined through amplification of the HBV’s S gene, by the nested-PCR technique and the fragment sequencing. Sixty six porters of chronic hepatitis B participated of this study, resulting in 11,92% of 503 reported cases in Roraima. The age average among the participants was 44,5 years old; men and women presented the same risk of exposition to HBV and 51,28% completed high school indicating that the lower instruction level, the higher the infection chance. It was statistically related to HBV´s infection risk, the use of illegal drugs; sexual risk behavior;Owning familiar contact with hepatitis B porters and accidents with cutting and piercing equipment. The genotype A was the most prevalent in the sequenced samples of Roraima, representing 91,67%, followed by genotype D with 8,33%. Subgenotypes A1, A2 and D2 was also identified.